Development and validation of spectrophotometric and HPTLC methods for simultaneous determination of rosiglitazone maleate and metformin hydrochloride in the presence of interfering matrix excipients. (September 2014) - Mahgoub, Hoda; Youssef, Rasha M.; Korany, Mohamed A.; Khamis, Essam F.; Kamal, Miranda F.
Abstract Two simple methods have been developed and validated for the simultaneous determination of rosiglitazone maleate (ROS) and metformin hydrochloride (MET) in synthetic mixtures and coated tablets in a ratio of 1:250 (ROS:MET). The first method was a spectrophotometric one. The minor component, ROS was determined by measuring the values of absorbance at λmax 312 nm and the D1 amplitudes at 331 nm where MET shows no absorption contribution. However, absorbance interferences from tablet excipients were successfully corrected by D1 at 331 nm zero-crossing technique. Study of spectral interference from tablet excipients was included in the text. Standard curves for Amax and D1 methods were in the concentration range 20.0–80.0 μg mL−1. The major component, MET was determined both in binary mixtures and tablets by measuring its Amax at 236 nm. Extensive dilution eliminated any absorption contribution from the coexisting ROS or tablet matrix. Standard curves showed linearity in the concentration range 4.0–12.8 μg mL−1. The second method was based on high performance thin layer chromatography (HPTLC) separation of the two drugs followed by densitometric measurements of their spots at 230 nm. The separation was carried out on Merck HPTLC aluminium sheets of silica gel 60 F254 using methanol:water:NH4Cl 1% w/v (5:4:1 v/v/v) as the mobile phase. Linear calibration graphs of peak area values were obtained versus concentrations in the range of 0.4–2.0 μg band−1 and 20.0–100.0 μg band−1 for ROS and MET, respectively. According to International Conference on Harmonisation (ICH) guidelines, different validation parameters were verified for the two methods and presented.